Pragmatic markers and peripheries - Van Olmen, Daniël; Šinkuniene, Jolanta (Pragmatics & beyond, 2021)
"The relation between pragmatic markers and the peripheries of clauses, utterances and/or turns has been a topic of linguistic interest for the last few decades. Many issues continue to be debated, however, such as "how should the notion of periphery be defined?", "to what extent do pragmatic markers in the left versus the right periphery fulfill different functions?" and "which factors determine the order of multiple pragmatic markers in a periphery?". This volume brings together a number of studies addressing these and other questions. It presents new data from a diverse range of languages - including less researched ones in this context like Ainu, Latvian and Lithuanian - and on a variety of types of pragmatic marker - including emoji. The volume as a whole offers new insights into, among other things, the subjectivity intersubjectivity peripheries hypothesis, the idea of left-to-right movement and the matrix clauses hypothesis"--